Loss, Gain and Altered Function of GlyR α2 Subunit Mutations in Neurodevelopmental Disorders - Chen, Xiumin; Wilson, Katie A.; Schaefer, Natascha; De Hayr, Lachlan; Windsor, Mark; Scalais, Emmanuel; van Rijckevorsel, Germaine; Stouffs, Katrien; Villmann, Carmen; O’Mara, Megan L.; Lynch, Joseph W.; Harvey, Robert J. (Frontiers in Molecular Neuroscience, 2022)
Glycine receptors (GlyRs) containing the α2 subunit govern cell fate, neuronal migration and synaptogenesis in the developing cortex and spinal cord. Rare missense variants and microdeletions in the X-linked GlyR α2 subunit gene (GLRA2) have been associated with human autism spectrum disorder (ASD), where they typically cause a loss-of-function via protein truncation, reduced cell-surface trafficking and/or reduced glycine sensitivity (e.g. GLRA2∆ex8-9 and extracellular domain variants p.N109S and p.R126Q). However, the GlyR α2 missense variant p.R323L in the intracellular M3-M4 domain results in a gain-of-function characterized by slower synaptic decay times, longer duration active periods and increases in channel conductance. This study reports the functional characterization of four missense variants in GLRA2 associated with ASD or developmental disorders (p.V-22L, p.N38K, p.K213E, p.T269M) using a combination of bioinformatics, molecular dynamics simulations, cellular models of GlyR trafficking and electrophysiology in artificial synapses. The GlyR α2V-22L variant resulted in altered predicted signal peptide cleavage and a reduction in cell-surface expression, suggestive of a partial loss-of-function. Similarly, GlyR α2N38K homomers showed reduced cell-surface expression, a reduced affinity for glycine and a reduced magnitude of IPSCs in artificial synapses. By contrast, GlyR α2K213E homomers showed a slight reduction in cell-surface expression, but IPSCs were larger, with faster rise/decay times, suggesting a gain-of-function. Lastly, GlyR α2T269M homomers exhibited a high glycine sensitivity accompanied by a substantial leak current, suggestive of an altered function that could dramatically enhance glycinergic signaling. These results may explain the heterogeneity of clinical phenotypes associated with GLRA2 mutations and reveal that missense variants can result in a loss, gain or alteration of GlyR α2 function. In turn, these GlyR α2 missense variants are likely to either negatively or positively deregulate cortical progenitor homeostasis and neuronal migration in the developing brain, leading to changes in cognition, learning and memory.